Propagation Technique of Pasak Bumi (Eurycoma longifolia Jack) Via Shoot Cutting - Arida Susilowati; Supriyanto Supriyanto; Iskandar Z. Siregar; Atok Subiakto (FORESTA, 2012)
Pasak bumi (Eurycoma longifolia Jack) is a treelet growing wildly in the forests of Southeast Asia and widely used throughout the region because of its medicinal properties. Uncontrolled harvesting of wild-grown trees has led to rapid decrease of natural populations. The objective of this research was to get information about propagation technique of pasak bumi by shoot cutting and its adventitous root formation. Cutting materials were originated from 7 month aged seedling propagated by seed. Media used were combination of cocodust : ricehusk (1:1 v/v), cocodust : ricehusk (1:1v/v) and cocodust : ricehusk (2:1 v/v). Research showed that medium significantly improved secondary root length, while rooting percentage, primary root length and the number of root significantly was affected by Rootone F treatment. The microtechnique result showed that roots were first developed from the mesristematic cambium cells.Keywords: Eurycoma longifolia Jack, propagation technique, shoot cutting